2001
DOI: 10.1136/pmj.77.911.582
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine deficiency in patients with B-chronic lymphocytic leukaemia: a pilot study

Abstract: Malignancy associated primary thiamine deficiency has been documented in several experimental tumours, sporadic clinical case reports, and in a number of patients with fast growing haematological malignancies.Thiamine status was assessed prospectively in 14 untreated B-chronic lymphocytic leukaemia (CLL) patients, and in 14 age matched control patients with nonmalignant disease. Patients with any known cause of absolute, relative, or functional thiamine deficiency were excluded.High (>15%) thiamine pyrophospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 14 publications
1
26
1
1
Order By: Relevance
“…Higher rates of TD among patients with cancer have been reported in several small studies. 5,24 WKS has also been reported in cancer. The prevalence of WKS in patients who died following bone marrow transplants has been estimated in 2 studies, with estimates ranging from 6–33%.…”
Section: Introductionmentioning
confidence: 95%
“…Higher rates of TD among patients with cancer have been reported in several small studies. 5,24 WKS has also been reported in cancer. The prevalence of WKS in patients who died following bone marrow transplants has been estimated in 2 studies, with estimates ranging from 6–33%.…”
Section: Introductionmentioning
confidence: 95%
“…Thiamine deficiency is also reported in a significant proportion of patients with leukaemia. Of 14 chronic lymphatic leukaemia patients, 37.5% had thiamine deficiency although there were no obvious clinical manifestations [20]. The authors speculated that the primary thiamine deficiency is promoted by the increased leucocyte count, which may increase thiamine consumption.…”
Section: Clinical Scenariosmentioning
confidence: 99%
“…Increased serum pyruvate can also be caused by deficiencies in thiamine, the physiologically active form of which, thiamine pyrophosphate, acts as a coenzyme in pyruvate decarboxylation. Seglimann et al 62 have reported comparatively high rates of thiamine deficiency in CLL patients and have proposed that this may be due to increased whole body requirements of energy and thiamine, increased thiamine consumption by tumour cells and finally, impaired thiamine phosphorylation. Although detectable using 1 H-NMR, serum concentrations of thiamine were too low to be assessed in this study.…”
Section: Classification Methodsmentioning
confidence: 99%